2019
DOI: 10.22159/ijap.2020v12i2.34846
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Optimization of Curcumin Solid Dispersion Pellets for Improved Solubility

Abstract: Objective: The present study was aimed at designing of solid dispersion based pellets of curcumin (Cu) for improving its solubility. Methods: Solid dispersion (SD) of Cu was prepared by the melt method using Poloxamer 407 (Pol 407) at a different weight ratio of Cu-Pol 407 (1:2, 1:3, 1:5, 1:7, 1:10). The solid dispersion was characterised by FTIR, SEM, DSC, XRD and evaluated for saturation solubility in water, drug content and in vitro dissolution. The pellets of Cu solid dispersion were prepared by extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The most preferable processing can be done at temperature above the M.P. of semi-crystalline polymers or [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 ] °C above the glass transition temperature Tg of amorphous polymers, but below the M. P. of the crystalline API [ 80 , 81 ].…”
Section: Processing Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…The most preferable processing can be done at temperature above the M.P. of semi-crystalline polymers or [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 ] °C above the glass transition temperature Tg of amorphous polymers, but below the M. P. of the crystalline API [ 80 , 81 ].…”
Section: Processing Challengesmentioning
confidence: 99%
“…The solid dispersion of curcumin using different ratio of Poloxamer 407 by melt method were finally extruded and spheronize. The resulting pellets showed increase in solubilisation however it is noteworthy that pelletization process had no impact on solubilisation of solid dispersion [ 94 ], were formulated as pellets without any impact on drug release profile.…”
Section: Release Modifications For Different Applicationsmentioning
confidence: 99%
“…SEM photomicrograph of pellets revealed that the pellets were spherical shaped in nature and the surface was rough. This could be due to the deposition of fines produced by attrition of pellets during spheronization [26] [fig. 9].…”
Section: Surface Morphology (Sem Analysis)mentioning
confidence: 99%
“…Delayed-release pellets of omeprazole magnesium, which is unstable in stomach pH, hence formulated as delayed-release dosage form to allow absorption in intestinal pH [38]. Deshkar et al, designed curcumin solid dispersion pellets for improving the solubility of poorly soluble curcumin and observed a significant enhancement in dissolution compared to pure curcumin pellets [39]. Fielden et al, reported that particle size of lactose powder ( fine and coarse) has an effect on the extrusion characteristics of the wet mass and on the size and the roundness of the resulting pellets when prepared using cylinder extruder and a ram extruder [40].…”
Section: Drug and Excipientsmentioning
confidence: 99%